Engage for Equity: Advancing the Fields of Community‐Based Participatory Research and Community‐engaged Research in Community Psychology and the Social Sciences. Issue 3 (8th July 2021) - Wallerstein, Nina
Abstract: Community Based Participatory Research (CBPR), as the most cited Community‐Engaged Research (CEnR) approach in the health fields, mirrors community‐psychology's long‐term interest in participatory action research and community empowerment. This article introduces the Engage for Equity study, a long‐term National Institutes of Health‐funded inquiry to identify best partnering and collaborative practices that contribute to community capacity, empowerment and policy outcomes, and to long‐term improved health and health equity. Four articles present facets of the study: psychometrics of partnering process and outcome measures, measures and outcomes of shared governance, and description of the CBPR Model as a new equity‐ and partnership based implementation framework; and as a tool for organizational learning and quality improvement. Finally a review of CBPR and CEnR in psychology offers recommendations for the field. Though focusing on CBPR and CEnR, Engage for Equity offers lessons for all forms of participatory action research. Highlights: Engage for Equity research contributes a validated CBPR Model and measures for engaged research. Engage for Equity contributes new ways to use collective reflection tools to strengthen partnerships Our research has contributed learnings in psychometrics of measures of processes and outcomes E2 surveys of over 400 diverse partnerships provides major national evidence of best practices